1992
DOI: 10.1093/clinids/14.3.662
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Brain Abscess Possibly Due to Bacille Calmette-Guerin in an Immunocompromised Child

Abstract: Disseminated infection with bacille Calmette-Guérin (BCG) is rare, even in immunocompromised patients who receive BCG injections as immunotherapy or immunization. When such infection occurs, it is usually in patients with decreased cellular immunity. A 6-year-old Caucasian girl who was receiving maintenance chemotherapy for acute lymphoblastic leukemia presented with symptoms of meningitis. A temporal-lobe biopsy revealed acid-fast bacilli that were identified as Mycobacterium bovis BCG. Neither the patient no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…20,21 One child died, and two had favorable outcomes. In a case similar to those in this report, Coppes et al 22 described a six-year-old Canadian girl with leukemia in whom a BCG-related brain abscess and meningitis developed. No source of the BCG was identified.…”
Section: Discussionsupporting
confidence: 79%
“…20,21 One child died, and two had favorable outcomes. In a case similar to those in this report, Coppes et al 22 described a six-year-old Canadian girl with leukemia in whom a BCG-related brain abscess and meningitis developed. No source of the BCG was identified.…”
Section: Discussionsupporting
confidence: 79%
“…15 On the other hand, despite antituberculous therapy, patients with SCID invariably succumb to BCG infection unless the immune system is reconstituted. 5,17 In three of our patients, resolution of disseminated BCG infection occurred only after successful restoration of their immune function by allogeneic bone marrow transplantation from HLA-DR matched siblings. In these three patients, abscess developed at the BCG inoculation sites after the patients became immunocompetent.…”
Section: Discussionmentioning
confidence: 85%
“…Coppes et al 17 reported a case of M. bovis brain abscess and meningitis in a leukemic child who responded to treatment with isoniazid and rifampin. Similarly, other patients with BCG meningitis but no underlying immune defects were successfully treated with antituberculous therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Some recommend early excision of the abscess because the thick, fibrotic capsule of a fully developed tuberculous abscess prohibits catheter drainage, 12 while others consider prolonged anti-TB treatment adequate. 13 For this patient, the anti-TB treatment started early, as soon as the pulmonary TB had been diagnosed. Unfortunately, no bacilli were cultured from the pus at the time of stereotactic biopsy, but this may have been a consequence of the anti-TB treatment, even though it appeared to have been ineffective.…”
Section: Resultsmentioning
confidence: 99%